LITERATURE REVIEW: HUBUNGAN ANTARA POLA ASUH ORANG TUA DENGAN TINGKAT KEMANDIRIAN ANAK RETARDASI MENTAL - ilma Ayuningsi (PROFESSIONAL HEALTH JOURNAL, 2023)
Abstrack A mentally retarded child is a condition characterized by intelligence below average (IQ 86 and below) who will experience delays, one of which is self-care independence, so that the child becomes dependent on the family, especially the parents. Children with mental retardation should be more concerned about this, and parents should be more knowledgeable about how to care for these kids and possess stress management skills that they are likely to have gained from dealing with kids' personalities and behavior. The purpose of this study is to ascertain the association between parenting practices and the degree of independence in mentally retarded children. The design used is secondary data collection, namely literature reviews, articles are collected using search engines such as Scient Direct, IMJH, and Scholar. From the 3 databases, there were 1878 articles then screened according to the year of publication, duplicate titles, abstracts so that 10 articles were obtained. The criteria for the articles or journals used include parental care, independence of mentally retarded children, parental education, and articles published in 2015-2020. This review literature analysis is synthesized using a narrative method. Primarily based on the articles, the result display that pareting patterns can have an effect on the independence of kids with mental retadation in which children nevertheless want upbringing, steerage, and supervision from mother and father. Good parenting will have a positive effect on a child's ability to be independent. This study makes the recommendation that more research be done on the readiness of parents to become parents and the independence of children with more focused mental rehabilitation, as well as counseling about parenting and education readiness and how to care for and educate children with mental retardation.